KONDISI HIDRODINAMIKA DAN TRANSPOR SEDIMEN DI MUARA SUNGAI PALU - Mohammad Lutfi; Markus Lumbaa; Risna Risna (Sekolah Tinggi Teknologi MIGAS, 2021)
Sedimentation at the mouth of the Palu River is the cause of frequent flooding in Palu City. This study aims to understand the hydrodynamic conditions and longshore sediment transport around the mouth of the Palu River. Hydrodynamic conditions were analyzed by measuring velocity and current direction, salinity, discharge, breaking wave height, breaking wave depth, wave incidence angle, water density, and water depth. While the amount of longshore sediment transport was calculated based on the CERC empirical formula. The results revealed that the distribution of currents at the mouth of the Palu River was dominated by river currents, where the amount of seawater in the mouth of the river was small. This could be seen from the small salinity value, which ranged from 1 ‰ to 5 ‰. The longshore sediment transport around the Palu River estuary is 36.06 m3/day, where this sediment resulted in silting at the Palu River estuary during deposition.